Integrasi psikologi dengan Islam: menuju psikologi Islami - Hanna Jumhana Bastaman (Pustaka Pelajar, 1997)
ws.c.1-2/ast c.3/ir,c.4/ir,c.5/tr,c.6/ir,c.7/oen, c.8 /sn,c.9-11/ir,c.12/en, c.13-14/wk, stock=c.15